COMPARISON OF THE SHORT-TERM EFFECTS OF KETOROLAC AND PARACETAMOL IN THE MANAGEMENT OF INTRA-ANESTHESIA PAIN : Literature Review - FELISHA SOFYAN; Nadya Ulhaqisya; Diva Aurelia; Kirana Marhana (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
Background: Postoperative pain is a global challenge affecting nearly half of patients, potentially leading to chronic pain. The development of non-opioid multimodal analgesia strategies, particularly the pre-emptive or intra anesthetic use of intravenous Ketorolac and intravenous Paracetamol, is key to managing short-term pain. This study aims to map, categorise, and compare the short-term efficacy of intravenous Ketorolac and intravenous Paracetamol administered in the intra-anesthetic context for various types of surgery. Methods: This study uses a Scoping Review design based on the Arksey and O'Malley framework, and is reported according to the PRISMA-ScR guidelines. A literature search was conducted on major databases for studies published between 2020 and 2025. Data was extracted using the PICOST framework (Population, Intervention, Comparison, Outcome, Study Type, Timeframe) and synthesised narratively and thematically based on the surgical context. Results: Ten primary studies (RCTs and comparative) were included, focussing on short-term efficacy. The results showed that the combination of Ketorolac (30 mg) and Paracetamol (1 g) significantly reduced total morphine requirements post-laminectomy compared to Paracetamol monotherapy (P < 0.05). In major surgery (CABG), paracetamol monotherapy is effective in reducing VAS scores better than ketorolac (P < 0.05) and in reducing morphine consumption (P < 0.001). Studies confirm the feasibility of pre-emptive/intra-anesthetic administration for both agents (Kashif et al., 2021). Conclusion: The optimal strategy for short-term postoperative pain management is a multimodal approach combining intravenous Ketorolac and Paracetamol, initiated during the intra-anesthetic phase, to effectively reduce opioid requirements and improve the quality of postoperative analgesia.